Comparing the best athletic performances of the two sexes - Grammaticos, B.; Charon, Y. (New Studies in Athletics, 2014)
This paper addresses the question of the gender dependence of athletic performances. The comparison of women's to men's performances shows 1) there is a strong dependence of the ratio of the performance to the world ranking of the performer in both genders and 2) this dependence is smooth to the point that it allows the introduction of a simple model that makes it possible to recover the ratios of the world records with precision. The analysis shows a significant difference in gender dependence between running and jumping events. Finally, the temporal evolution of the ratio of men's-women's performances is examined. While in some cases the world record ratio is stationary, in disciplines like the triple jump, only relatively recently introduced for women, the ratio of the 50th performers shows a constant improvement of the results of the women compared to those of the men of the same rank. The results lay the basis for a systematic approach to the analysis of athletic performances and in particular to the comparison of the gender dependence of the latter.